O uso de dispositivos eletrônicos móveis como Tecnologia Assistiva por pessoas com baixa visão - Borges, Wanessa Ferreira (Universidade Federal de São Carlos, 2019)
The access to the visual information present in several social spheres, demand a good functioning of the visual system. The absence and / or reduction of their performance can cause disadvantages in the development, functionality and social participation, particularly when considered the people with low vision or blindness. On the other hand, the visual abilities and the use of the remaining senses can be leveraged for access to information through the use of Assistive Technology (AT). Although the beneficial potential of conventional AT features is proven, onlye a fraction of people with low vision do not use them in promoting their functionality, due to lack of knowledge, economic barriers and because these resources mark the disability. Simultaneously, smartphone and tablet apps present themselves as possibilities in AT and their use has become popular among people with low vision. In this context, the present study aimed to identify and characterize, from the perspective of people with low vision, smartphone and / or tablet apps that assume the function of AT features in occupational activities, regarding their functionalities, potentialities, limitations and new creative demands. The methodology used in this research has a descriptive nature, under the case study design. The study included 28 people with low vision who are members of an existing WhatsApp group. The data collection took place in the virtual space of this app, individually, through a semi-structured interview. The data were transcribed, and analyzed based on the grounded theory, which made possible the following units of analysis: used apps; functionality; difficulties in using; strengths; negative points; creative demands. The participants cited 50 applications and nine accessibility features used on smartphones and tablets. In terms of functionality, the apps that stood out were the ones used for access to textual, print or digital content and the ones used to conduct domestic navigation activities, self-care, food and shopping, recreation and socialization, communication, contrast, and labor and academic activities. The difficulties of handling the apps were associated with: identifying and maintaining the correct focal distance, framing the image to be captured, enabling and disabling accessibility features when exchanging different tools, complexity in navigation gestures and difficulties in the transfer and first access to the app. The positive points were linked to their function, practicality and independence provided to users. The negative points related to the factors that hindered access and use, and the need for internet, battery. The demands for app creation involved browsing activities, reading printed content, labels, price and menu labels, finding products in supermarkets, recognizing people, finding objects, offering and searching for jobs, and professional performance. From this survey, it was possible to identify the potential of these apps in the solution of difficulties faced by people with low vision. In this way, more research, investments, dissemination and teaching programs are suggested to increase its use.
Keywords: Dispositivos eletrônicos móveis; Tecnologia Assistiva; Deficiência visual; Aplicativos; Recursos de acessibilidade; Educação Especial; Mobile electronic devices; Assistive Technology; Visual impairment; Apps; Accessibility features; CIENCIAS HUMANAS